PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH SISWA MELALUI MODEL PEMBELAJARAN CONCEPT ATTAINMENT BERBANTUAN MEDIA KOTAK PINTAR - Aisyatul Ummah; Zulmi Roestika Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Concept Attainment learning model assisted by the "Kotak Pintar" (Smart Box) media on students' problem-solving abilities. The research method used is quantitative with a Non-Equivalent Control Group Design. The population in this study was all students of MI Sabilul Huda. The research sample consisted of class IVB as the experimental group and class IVA as the control group. Data collection techniques included tests (pretest and posttest) and non-test techniques such as observation questionnaires and documentation. Data analysis was carried out using normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant difference in the use of the Concept Attainment model assisted by Smart Box media on students’ problem-solving abilities. This is evidenced by the significance value of 0.000 < 0.05 in the independent sample t-test, indicating a difference in learning quality between the experimental and control classes. The average score of the experimental class was 94.07, which was significantly higher than the control class average of 67.27.